KEDUDUKAN HUKUM PERUSAHAAN MODAL VENTURA ASING DALAM MELAKUKAN PEMBIAYAAN SECARA LANGSUNG TERHADAP USAHA DI INDONESIA - , MIREZA FITRIADI; , Prof. M. Hawin, S.H., LL.M., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are many ways of foreign investment in Indonesia, one of them is by financial institutions mechanism. Those mechanism are applied by the most popular method in the world, which is Venture Capital (VC) investment. Laws and regulations that exist in Indonesia only regulate foreign VC with Indonesian legal entity, and not regulating direct foreign VC. This research aims to determine the implementation of direct foreign VC investment in Indonesia. This research also aims to determine what institution which authorized to supervise the foreign direct venture capital investment. The research is a qualitative study with statute approach. We conduct the research by secondary data. The results of this study indicate that direct foreign VC investment is not the role of the Indonesia Financial Services Authority (OJK RI) to conduct surveillance.